Mitotically active fibrothecoma in association with sclerous peritonitis - Bdioui Ahlem; Ben Khlifa Sarra; Kaabia Ons; Missaoui Nabiha; Hmissa Sihem; Mokni Moncef (Annals of Cytology and Pathology - Peertechz Publications, 2020)
Background: Mitotically active fibrothecoma associated with sclerosing peritonitis is an enigmatic and rare condition, described by Clement et al. in 1994, with fewer than 50 pathologically characterized cases. Association of these two lesions is extremely rare and the etiology currently remains unclear; therefore, association with anti-epileptic drugs was suggested.  Case presentation: We report the case of young female, with history of epilepsy, presented with acute severe abdomenal pain. Ultrasound revealed a 20 cm mass, possibly arised from ovary, which was associated with septate ascites. The microscopic examination of the mass showed a morphology fibrothecoma with areas of oedema and high mitotique index but without severe atypia.  Conclusion: Mitotically active fibrothecoma associated to sclerosing peritonitis is relatively rare condition. Although its disturbing presentation, the behavior of this rare condition is benign; therefore this entity should be well known by surgeon and pathologist to ovoid misdiagnosis and overtreatment of patient.